2003
DOI: 10.1136/adc.88.10.918
|View full text |Cite
|
Sign up to set email alerts
|

Management of thoracic empyema in childhood: does the pleural thickening matter?

Abstract: Aims: To determine the clinical course and long term outcome of empyema treated without decortication. Methods: Fourteen consecutive admissions to one hospital were studied; radiological resolution and lung function were subsequently followed. The children were aged 2-14 years. All were treated with intravenous antibiotics and chest drain only. Results: All patients had extensive pleural thickening evident on chest x ray examination at the time of discharge, which resolved entirely over a period of 2-16 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 22 publications
5
56
2
4
Order By: Relevance
“…(36,37,38) In the present study, all patients responded to conservative management and one patient required decortication and one requiring VATS. Previous studies suggest a success rate of 61-100% with chest tube drainage and antibiotics.…”
Section: Discussionmentioning
confidence: 96%
“…(36,37,38) In the present study, all patients responded to conservative management and one patient required decortication and one requiring VATS. Previous studies suggest a success rate of 61-100% with chest tube drainage and antibiotics.…”
Section: Discussionmentioning
confidence: 96%
“…no fever, normal breath sounds, resonant percussion note and x-ray evidence. Of the 6 which were cured with pleural thickening 17 , 4 cases did not show any further improvement during the follow up and two cases showed improvement to almost normal during the follow up. Of the two cases with pneumothorax one case improved with conservative management while the other case was lost for follow up.…”
Section: Age Distribution Of Empyema In Childrenmentioning
confidence: 89%
“…Radiological resolution following empyema in children varies widely. 11 Sonnappa et al 4 found that the majority of patients with treated empyema had abnormal CXRs at 6 months. Satish et al 11 found that complete radiological resolution was as variable as 2-16 months.…”
Section: Discussionmentioning
confidence: 99%